Do women benefit from FDI? FDI and labor market outcomes in Cambodia - Matthias Helble; Asami Takeda (Asian Development Bank Institute (ADBI), 2020)
Although we have solid empirical evidence on the impact of foreign direct investment (FDI) on various labor market outcomes, empirical studies on the effects on women remain very limited. This paper aims to contribute to this literature by examining the case of Cambodia. Using national household level data from the Cambodia Socio-Economic Survey, we assess how FDI affects women's wages and formality compared to men in the manufacturing sector. We compare outcomes in the garment sector and in all other manufacturing sectors. We use exogenous variations of inward FDI across provinces linked to spatial differences in the initial industry's composition as an instrument to identify the causal effect of FDI on labor market outcomes. Our results indicate that FDI helps to increase wages and the probability of working in the formal sector, for both the garment sector and all other manufacturing sectors. However, we do not find evidence that FDI helps to reduce the gender wage gap in either.
Keywords: F16; J31; 330; foreign direct investment; labor market; gender; Cambodia